A Sociolinguistic Analysis of Oath Terms Used by Jordanian Youths - Thneibat, Amal (Dirasat: Human and Social Sciences, 2023)
Objectives: The aim of the study is to investigate oath terms used by Jordanians in relation to different variables, such as gender and situation. The terms are analyzed based on their thematic associations concerning the two variables of gender (speaker and hearer) and situation (formal and informal), where the speaker is of a similar status in the informal situation and of a higher status in the formal one. Methods: The data was collected through a Data Completion Task (DCT) involving 50 Jordanian university students as respondents. The questionnaire was analyzed both qualitatively and quantitatively, with the significance difference calculated at (α=0.08). Results: The study found that religious terms are the most frequent in all cases, suggesting that changing the variables does not significantly influence their frequency. On the other hand, other categories of swearing terms are culturally bound and are influenced by the social variables of gender and situation in the Jordanian context. Conclusions: Future research may focus on exploring other social variables that could influence the usage of oath terms, such as various age groups and levels of education. Additionally, the study could be expanded as a contrastive analysis, comparing the terms used by individuals from different languages and cultural backgrounds.